Microwave-Based Technique for Determination of Cholesterol in Milk Products - Abu Jahar, Noorhasmiera (2011)
A new method for determination of cholesterol in milk products has been developed based on dielectric properties of the cholesterol enzymatic reaction at microwave frequencies in the range of 0.2-20 GHz. The dielectric properties of cholesterol solutions, enzyme and the product of cholesterol-enzyme reaction were measured using an Open Ended Coaxial Probe (OECP) coupled with automated network analyzer (ANA) at room temperature (25C). At frequency 4.98GHz and 10.9GHz the dielectric loss difference was obtain by subtracting the dielectric after the enzymatic reaction of cholesterol with dielectric of cholesterol oxidase alone. The cholesterol to cholesterol oxidase ratio at 1:2 is the best experimental condition for the detection of cholesterol using this system. The relative standard deviation (RSD) of the reproducilibity was calculated to be 1.85% for frequency 4.98 GHz and 2.06% for frequency 10.9 GHz at concentration of 38.67 ppm. The limit of detection was calculated to be 0.83 ppm at frequency 4.98GHz and 1.18 ppm at frequency 10.9 GHz. The results obtained from the developed method were compared with the standard method of cholesterol determination (BOHAC extraction- HPLC). The comparison result shows a poor agreement between the developed method and tandard method. The value of tcalc > ttable at 95% confidence level, thus, there is significant difference between both techniques at this confidence level. This may be due to interference of other compound such as protein, calcium, water and carbohydrate in the milk that affects the dielectric loss and because dielectric loss is too sensitive compared to dielectric constant.